Multi-proxy Archaeobotanical Analysis from Mesolithic and Early Neolithic Sites in South-west Ukraine. (4th May 2021) - Salavert, Aurélie; Gouriveau, Emilie; Messager, Erwan; Lebreton, Vincent; Kiosak, Dmytro
ABSTRACT: This paper presents the results of archaeobotanical studies carried out on the Late Mesolithic layer at Melnychna-Krucha (6460–6100 cal BC) and the Linearbandkeramik (LBK) site of Kamyane-Zavallia (5295–4960 cal BC), close to the Southern Bug River. Despite the relatively modest dataset presented in this paper, these preliminary results provide new data for a region where the environmental setting and the uses of plant resources during the Early Atlantic period are poorly understood. The main taxa used for firewood are quite similar at Melnychna-Krucha and Kamyane-Zavallia, although they were occupied 1000 years apart. Fraxinus (ash) and Quercus (oak) dominate both charcoal assemblages . These taxa, as well as Ulmus (elm), could have grown together in the alluvial deciduous forest, probably on the Southern Bug riverbank, close to both sites. Carpinus (hornbean) was present but probably still not abundant around Kamyane-Zavallia at the end of the 6th millennium. Macroremains and phytoliths demonstrate that the plant production economy (cultivation, cereal processing) was well developed and very similar to other European LBK sites. At Melnychna-Krucha, plant macro- and microremains did not indicate a productive subsistence.